PENGARUH METODE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN MEMBACA DAN MENULIS KELAS 1 - Purwanto, Faisal Ahmad; Setiyadi, Dwi Bambang Putut; Sri Suwartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low reading and writing skills of first-grade elementary school students, which are caused by the use of conventional teaching methods that are unable to adequately accommodate the characteristics of the students. The purpose of this study is to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) method on the reading and writing skills of first-grade students at SD N 2 Jatipuro in the 2025/2026 academic year. The type of research used is quantitative research with a quasi-experimental design (nonequivalent control group design). The subjects of this study were 40 students, consisting of 20 students in the experimental class and 20 students in the control class. Data collection techniques included tests (pre-test and post-test) and observation. Based on the research results and discussion, it was found that the students’ reading and writing skills improved after the implementation of the CIRC method. This is evidenced by the significance value of the t-test, which indicates p < 0.05, thus accepting the alternative hypothesis (Ha).Therefore, it can be concluded that the Cooperative Integrated Reading and Composition (CIRC) method has a significant effect on the reading and writing skills of first-grade students.